Self-aware robots : on the path to machine consciousness - Takeno, Junichi (Singapore : Jenny Stanford Publishing, 2022)
This book focuses on the research and development in the field of self-aware robots. Its theme is artificial consciousness, a field that covers both artificial intelligence and robotics, and includes philosophy, psychology, the study of biological evolution, physiology, and medicine, especially brain neuroscience and neuropsychiatry.
1. Introduction 2. StoryofRobots 3. Story of the Human Brain 4. Human Consciousness and the Mind 5. Professor Valentino Braitenberg's Vehicles 6. Professor Rodney Brooks' Robots 7. Artificial Neural Networks and Machine Evolution 8. Machine Consciousness 9. New Architecture of Robot Consciousness and the Robot Mind 10. Physical Demonstration of Successful Mirror Image Cognition by a Robot 11. Further Developments 12. Conclusions
OCLC-licensed vendor bibliographic record.
Keywords: Robotics; Artificial intelligence; TECHNOLOGY / Robotics